We Are the Champions? Performing whiteness in ASCENSION: DAWN OF CHAMPIONS. (October 2021) - Harrer, Sabine
Background: Building on previous studies on racism and whiteness in video games, this article investigates howdeck building games provide platforms for identity tourism, the symbolic appropriation of marginalised experiences, through their coupling of mechanics and racial stereotypes. Aims: The aim is to contribute to our understanding how dominant ideologies are expressed through simulation and gaming in a deck building context and how games similar to ASCENSION: DAWN OF CHAMPIONS (henceforth A: DOC) perpetuate racism and coloniality through gameplay design. This is part of an ongoing game studies effort to critique white supremacist and imperial structures in games. Method: In this article, I conduct a first-person close reading of A: DOC as an emblematic case study for contemporary deck building design. Using critical whiteness theory, I pay special attention to the gameplay design of the four Champion characters Nairi, Kor, Sadranis, and Dhartha in order to demonstrate the interplay of ludic, racial, and social performative elements in the construction of playful identities. Analysis: The deck building principles of A: DOC provides a racial pedagogical arena which creates affective links between gameplay and white supremacist values. In coupling digital deck building mechanics with stereotypical fantasy characters, the game invites players to take the roles of fantasy tourists and thereby become implicit in white supremacist play. Even though the characters Nairi, Kor, Sadranis and Dhartha are leaders of different genders and races, their "diversity" is established via popular racial cybertypes like the white female diversity advocate, the technologically advanced white male emperor, the aggressive Black male, and the Asian male exotic Oriental.